2022
DOI: 10.1111/eos.12861
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland involvement and oral health in patients with coeliac disease

Abstract: Coeliac disease (CD) is a chronic immune‐mediated enteropathy triggered by ingestion of gluten. The aim of this study was to investigate if the salivary glands as a component of the mucosal immune system are involved in CD, leading to sialadenitis and salivary gland dysfunction and associated oral manifestations. Twenty patients with CD aged 49.2 (SD 15.5 years) and 20 age‐ and gender‐matched healthy controls underwent an interview regarding general and oral health, serological analysis, a clinical oral examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
0
11
1
3
Order By: Relevance
“…[ 147 , 149 ]. The enteropathy triggered by the ingestion of gluten is correlated with various oral manifestations such as xerostomia, dry lips, mucosal ulcerations, and sialadenitis [ 150 ]. A recent pediatric study confirmed that children with CD have a higher rate of recurrent aphthous stomatitis and dental enamel defects than the healthy population [ 151 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 147 , 149 ]. The enteropathy triggered by the ingestion of gluten is correlated with various oral manifestations such as xerostomia, dry lips, mucosal ulcerations, and sialadenitis [ 150 ]. A recent pediatric study confirmed that children with CD have a higher rate of recurrent aphthous stomatitis and dental enamel defects than the healthy population [ 151 ].…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the other seventeen studies [11,[20][21][22][23][24]26,30,31,33,34,36,[39][40][41][42]44] presented data indicating that the occurrence of RAS in the study group was statistically significantly higher when compared to the control group.…”
Section: Recurrent Aphthous Stomatitis (Ras)mentioning
confidence: 99%
“…Niekonsekwentne jej przestrzeganie może prowadzić do osteoporozy, bezpłodności oraz nowotworów złośliwych, w tym chłoniaka T-komórkowego. Ponadto może występować z innymi chorobami autoimmunologicznymi, zwłaszcza cukrzycą typu 1, chorobami tarczycy i zespołem Sjögrena [7]. Celiakia może dotyczyć osób obu płci w każdym wieku, natomiast średni wiek rozpoznania to 45 lat, a do 20% wszystkich pacjentów diagnozowanych jest powyżej 60 roku życia [8].…”
Section: Wprowadzenieunclassified
“…Zmniejszone wydzielanie śliny jest możliwym objawem celiakii [2].Obniżenie wilgotności błony śluzowej jamy ustnej zwiększa ryzyko infekcji oraz próchnicy oraz wiąże się tez z zaburzeniami smaku. [2,7]. Badania wykazują, że mniejsze gruczoły śluzowe u pacjentów chorujących na celiakie charakteryzują się atrofią, włóknieniem i rozlanym przewlekłym zapaleniem.…”
Section: Iiif Zmniejszone Wydzielanie śLinyunclassified
See 1 more Smart Citation